2002
DOI: 10.1063/1.1510179
|View full text |Cite
|
Sign up to set email alerts
|

Bonding and mechanical properties of ultrathin diamond-like carbon films

Abstract: Structural and mechanical properties of diamond-like carbon films deposited by direct current magnetron sputtering J. Vac. Sci. Technol. A 21, 851 (2003); 10.1116/1.1575231Preparation and mechanical properties of composite diamond-like carbon thin films Ultrathin 2-nm-thick carbon coatings are needed to increase the storage density in magnetic hard disks. We show how x-ray reflectivity, surface Brillouin scattering, resonant Raman scattering, and electron energy loss spectroscopy can measure consistently the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 18 publications
3
51
0
3
Order By: Relevance
“…Связи sp 3 метастабильны и могут быть неустойчивы особенно на поверхности пленки. Экспе-риментальные исследования показывают, что в поверх-ностном слое толщиной 1 нм, доля sp 3 связей меньше, чем в центральной части пленки [2]. Кроме того поверх-ность ta-C пленки стремится к минимуму оборванных связей, поэтому можно ожидать переход sp 3 связей в sp 2 связи с образованием плоских комплексов с кольцевой структурой.…”
Section: образование графитовой фазыunclassified
“…Связи sp 3 метастабильны и могут быть неустойчивы особенно на поверхности пленки. Экспе-риментальные исследования показывают, что в поверх-ностном слое толщиной 1 нм, доля sp 3 связей меньше, чем в центральной части пленки [2]. Кроме того поверх-ность ta-C пленки стремится к минимуму оборванных связей, поэтому можно ожидать переход sp 3 связей в sp 2 связи с образованием плоских комплексов с кольцевой структурой.…”
Section: образование графитовой фазыunclassified
“…In some cases a well defined minimum of ( ) 2 , E χ ν is found, allowing a good identification of the parameters (Beghi et al, 2001;Comins et al, 2000;Zhang et al, 2001a), while in other cases a broad, valley-shaped minimum is found. In such cases a good identification of the parameters is not possible (Beghi et al, 2002;Zhang et al, 1998), although sometimes some combination of the parameters can be identified with better precision than individual parameters (Comins et al, 2000;Zhang et al, 1998Zhang et al, , 2001a. When several acoustic modes are measured, the larger amount of available information allows a precise and complete elastic characterization, as obtained e.g.…”
Section: Brillouin Spectroscopymentioning
confidence: 99%
“…This gives Brillouin spectroscopy an intrinsically higher sensitivity to the properties of films, or to the perturbation induced by the presence of very thin films. Brillouin spectroscopy was exploited to characterize tetrahedral amorphous carbon films of thicknesses of hundreds of nanometres (Chirita et al, 1999), tens of nanometres (Ferrari et al, 1999), down to a few nanometres (Beghi et al, 2002). It was also shown that inelastic light scattering can be sensitive to nanometric thickness differences (Lou et al, 2010).…”
Section: Brillouin Spectroscopymentioning
confidence: 99%
“…Physical phenomena (graphitization, spallation, and evaporation) taking place during the lasermatter interaction are characterized by different threshold intensities [4], which strongly depend on the pulse duration [5][6][7], the quantum energy, the number of pulses, and the properties of a-C:H films [8][9][10][11]. Cappelli et al [9] demonstrated that the treatment of the amorphous carbon films leads to the sp 3 → sp 2 transformation, aromating clustering, and formation of graphite nano-structures.…”
Section: Introductionmentioning
confidence: 99%
“…Amorphous carbon films are prospective materials for many applications because of their unique physical and chemical properties [1][2][3]. The pulsed laser's irradiation could achieve extremely high heating rates in the irra-diated spot of the processed material.…”
Section: Introductionmentioning
confidence: 99%